EVALUATION OF PATIENT EXPOSURE IN FAST kVp SWITCHING DUAL ENERGY COMPUTED TOMOGRAPHY: PHANTOM STUDY. Issue 3 (15th February 2018) - Yagami, K; Miyoshi, T; Shigeyama, S; Takai, H; Tsukahara, Y; Matsumoto, K; Suzuki, R; Yasuda, N; Okada, H; Suzuki, S; Foley, S J
Abstract: The aim of this study was to evaluate the suitability of size specific dose estimates (SSDE) to estimate patient dose in Fast kVp switching dual energy CT. An anthropomorphic phantom (RAN-110) was repeatedly scanned (chest, abdomen and the pelvis) using a 64 detector row MDCT (Discovery CT750 HD, GE Healthcare, Milwaukee, WI, USA) with various CT parameters, including Fast kVp switching. Dosimetry was performed using thermo-luminescent dosimeters, positioned both superficially and within the phantom. SSDE was calculated for all slices of the anthropomorphic phantom using both the localiser and axial images. In Fast kVp switching, SSDE underestimated the measured absorbed dose for the chest/abdomen region ~35% at the maximum, but were in closer agreement for the pelvic region about within 10%. In single energy techniques, SSDE could not be applied in the estimation of organ doses, but in Fast kVp switching dual energy techniques, SSDE could be applied for anatomical regions with larger thicknesses.